Twilight of a hero and other works on Rizal - Crisostomo, Isabelo T. (Quezon City, Philippines : New Day Publishers, 1999)
1. Rizal y Alonzo, Jose 2. Heroes--Philippines. 3. Short stories, Philippine (English).
Twilight of a hero -- The letters -- Dilemma at Talisay -- The execution -- Reformer or revolutionary? -- Battle of giants -- The tragedy of Rizal and Leonor -- Sweet stranger -- Rizal's legacy to Asia.
Short stories.